A rare large symptomatic simple hepatic cyst - Banerjee, Rupjani (BMJ Publishing Group, 2013)
A fit and well 4-year-old girl presented with a 1-year history of abdominal distension, pain and vomiting with signs of non-shifting dullness on the right side of the abdomen. An abdominal CT revealed a 19 cm epigastric cyst that did not appear to connect to any solid organ and was therefore thought to represent a mesenteric cyst. However, laparotomy revealed that the cyst was arising from the liver. The cyst was resected and subsequent histology revealed a simple hepatic cyst. The patient has been well post-operation. The case represents the largest described simple hepatic cyst in the 0–16 years paediatric age group in Europe to date. We outline the epidemiology, embryology, key investigations and management options for these lesions.